2016
DOI: 10.1002/ejoc.201601119
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the 1,3,4‐Oxadiazole Core through Thermolysis of Geminal Diazides

Abstract: The thermolysis of geminal diazides derived from acylacetate compounds is an efficient tool for the rapid construction of the 1,3,4‐oxadiazole core. While a broad range of ethyl esters undergoes smooth transformation to the desired heterocycles that contain the ester moiety in moderate to high yields, the analogous tert‐butyl esters give rise to the oxadiazoles with acyl groups, presumably through a pathway of decarboxylation followed by a new acyl transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…Herein, we report on the chemoselective reaction of tertiary azides with BCN ( 1 ) in the presence of sterically demanding ADIBO ( 2 ), which can thus selectively be reacted with primary or secondary azides. So far, only a few SPAAC reactions with secondary or even tertiary azides have been reported . We hypothesized that primary, secondary, and tertiary azides exhibit similar reactivity with sterically non‐demanding cyclooctynes, but expected a significant decrease in reactivity for tertiary azides when reacting with sterically demanding dibenzocyclooctynes (Figure b).…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…Herein, we report on the chemoselective reaction of tertiary azides with BCN ( 1 ) in the presence of sterically demanding ADIBO ( 2 ), which can thus selectively be reacted with primary or secondary azides. So far, only a few SPAAC reactions with secondary or even tertiary azides have been reported . We hypothesized that primary, secondary, and tertiary azides exhibit similar reactivity with sterically non‐demanding cyclooctynes, but expected a significant decrease in reactivity for tertiary azides when reacting with sterically demanding dibenzocyclooctynes (Figure b).…”
Section: Figurementioning
confidence: 97%
“…So far,o nly af ew SPAAC reactions with secondary or even tertiary azides have been reported. [31][32][33][34] We hypothesized that primary,s econdary,a nd tertiary azides exhibit similarr eactivity with sterically non-demanding cyclooctynes, but expected as ignificant decreasei nr eactivity for tertiary azides when reacting with sterically demanding dibenzocyclooctynes( Figure 1b).…”
mentioning
confidence: 99%
“…In ar ecent report on the thermolysis of geminal diazides derived from acylacetate compounds, we found that the migration of the carbonylg roups is favored over the migration of esters and amides;i n this particular case, however,t he initially formed tetrazole intermediate undergoes af urther Huisgen rearrangement [30] that resultsi nt he construction of the 1,3,4-oxadiazole core. [31] Future studies will test the migration tendencies of other groups, with the goal to fully understand the synthetic potential of thermolysis reactions with geminal diazides.…”
Section: Resultsmentioning
confidence: 99%
“…Although the reaction was only tested with two substrates, leading to 26a and 26b (Scheme 8A), we showed decades later that this reaction is of general appeal, allowing for the oxadiazole synthesis with a reasonably broad scope (Scheme 8B). [ 44 ]…”
Section: Reactivities Of Geminal Diazidesmentioning
confidence: 99%